Drawing the Islamic Ethical Line between Medical Treatment and Cosmetic Enhancement in Tissue Engineering - Hashi, Abdurezak Abdulahi; Azharuddin, Nur Syamimi Mohd; Munirah, Sha'ban; Radzi, Muhammad Aa'zamuddin Ahmad (Malaysia Journal of Medicine and Health Science, UPM Press, 2021)
Tissue engineering is a field that is currently perceived as a tool of more than only to treat diseases, amplifying the range of human abilities and appearances in those without pathology. This study investigates the use of tissue engineering as an enhancement technology, particularly in cosmetic enhancement, and the underlying ethical consequences of such practices. This study uses content and textual analysis to examine the field of tissue engineering, enhancement technology and the ethical consequences. This study finds a subtle line between tissue engineering in medical treatment and cosmetic enhancement practices in the opinion of Muslim jurists. Tissue engineering in the form of treatment seems permissible as a part of medication, while the cosmetic practices of tissue engineering are seen as morally unjustified and thus problematic. For example, there has been an increasing number of practices abroad and in Malaysia, such as CeltiGraf, the full thickness bio-engineered human skin developed by one local university for cosmetic purposes. This overly commercialised biomedical paradigm of healthcare tends to medicalise completely healthy people. As such, this medicalisation and commodification of health result in social and financial cost as well as increased anxiety and risk for complication from further workups for incidental or clinically unimportant findings. The traditional notion of medicine as the art and science of preserving and restoring the bodily health of the patient should remain as the Islamic framework that guides the application of tissue engineering for medical treatment purposes.